The optimization of P-i-N power switching diode in term of reverse breakdown voltage and electrostatic disharge performance
The Power switching diode (P-i-N diode) is one of the widely used diode in high power semiconductor devices as circuit protection. This popularity comes from excellent reverse voltage blocking and better electrostatic discharge (ESD) performance. As a result, the exploration on the P-i-N power switching diode to make the device more robust and competitive in the market is boundless, which aims for continuous improvement on the electrical characteristics. In this thesis, the design structure of P-i-N power switching diode consist of a circular shape anode junction, an n-type bulk substrate and the epitaxial layer of silicon substrate that represent the intrinsic region is used. Two different type of reverse breakdown voltage range P-i-N power switching diode are discussed in this thesis which is 250 V and 300 V. Independently, the optimization of reverse breakdown voltage and ESD respectively is conducted using 250 V and 300 V respectively as both diode have different good and poor electrical performance. The improvement of both diodes are performed by process simulation and as well as the confirmation by the design of experiment (DOE) of physical wafers fabrication process. For the ESD analysis, the devices are then subjected to nondestructive and destructive test of the fabricated diodes. Initially, this thesis describes the research work to widen the operating range of the 250 V P-i-N power switching avalanche diodes that can be operated more than 300 V by exploring the effects of the thickness and resistivity of epitaxial layer during forward and reverse biasing. Purpose of widen the operating range is to be used in power distribution application instead of telecommunication application. The result shows that, the changes on a P-i-N type structure of the power switching avalanche diode can increase the reverse breakdown voltage performance to ~500 V, which is beyond 300 V during reverse bias. The improvement of reverse breakdown voltage is more than 65% from 250 V. In addition to the electrical characteristics operating range improvement in the thesis, the study of ESD improvement of 300 V reverse breakdown voltage P-i-N diode is demonstrated. A better ESD performance of the P-i-N diode is also achieved by changing the characteristic profile of the P+ anode junction of P-i-N diode. The characteristics profiles are altered by lightening the dopant concentration and increasing the depth of the P-i-N diode junction. It is found that, the 300V P-i-N power switching diode can sustain more than 1 kV during ESD Human Body Modal (HBM) surge test (400% higher from initial surge) and more than 400 V during ESD Machine Modal (MM) surge test (100% higher from initial surge).